1992
DOI: 10.1128/jcm.30.7.1696-1702.1992
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-field gel electrophoresis of NotI digests of leptospiral DNA: a new rapid method of serovar identification

Abstract: Fingerprints for 72 reference serovar strains of pathogenic Leptospira spp. were obtained by pulsed-field gel electrophoresis (PFGE) following NotI restriction digests of the chromosome. These strains included the serovar reference strains of serogroups Australis, Ballum, Bataviae, Grippotyphosa, Panama, Pomona, and Pyrogenes. Sixty-four serovars could be identified by a unique NotI restriction profile. The remaining serovars were differentiated by chromosomal digestion with SgrAI. These included four serovars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(65 citation statements)
references
References 26 publications
4
57
1
3
Order By: Relevance
“…This result con¢rms the already observed antigenic and genetic di¡erentiation according to the host speci¢city of certain Pomona ¢eld strains [20]. In addition, PFGE was not able to discriminate between serovars copenhageni and icterohaemorrhagiae as previously reported [12]. However, PFGE showed in this case, through repeated observations, a pattern diversity within the serovar icterohaemorrhagiae, unless A02 represents a new serovar or genotype.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This result con¢rms the already observed antigenic and genetic di¡erentiation according to the host speci¢city of certain Pomona ¢eld strains [20]. In addition, PFGE was not able to discriminate between serovars copenhageni and icterohaemorrhagiae as previously reported [12]. However, PFGE showed in this case, through repeated observations, a pattern diversity within the serovar icterohaemorrhagiae, unless A02 represents a new serovar or genotype.…”
Section: Discussionsupporting
confidence: 83%
“…They can identify strain di¡erences either at the (sub)ser-ovar level, namely with pulsed-¢eld agarose gel electrophoresis (PFGE) [11,12], or at both the species and subspecies levels with the arbitrarily primed polymerase chain reaction (AP-PCR) and mapped restriction site polymorphisms (MRSPs) in PCR-ampli¢ed rrs and rrl eubacterial ribosomal genes [13]. However, despite the good sensitivity and reproducibility of these genetic tools, further studies are required before their usefulness can be evaluated on a routine basis, considering they still fail to di¡erentiate between important serovars such as icterohaemorrhagiae and copenhageni that are genetically and epidemiologically very similar but antigenically diverse [12]. In conclusion, it is important to compare MAbs, as an accurate and simple serological method for antigenic analysis in epidemiological studies to these new genetic techniques which also give quick results but need special equipment, trying to assess their respective applicabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been successfully utilized to discriminate between closely related serovars of the Leptospira spp. (Herrmann et al 1992;Ciceroni et al 2002;Naigowit et al 2007;Galloway and Levett 2008). The aim of this study was to analyse Leptospira strains isolated from humans in São Paulo, Brazil by using PFGE combined with the microscopic agglutination test (MAT) in order to have an accurate and reliable method to compare and classify leptospires.…”
Section: Introductionmentioning
confidence: 99%
“…It could be readily concluded that PUSA belonged to a di¡erent serovar than the patoc serovar of PFRA. Indeed, NotI digestions in PFGE have been accepted since 1995 by the Leptospira Taxonomy Subcommittee as an alternative molecular technique for identi¢cation of leptospires at the serovar level [16]. Surprisingly, no distinct pro¢le could be obtained from PITAL DNA digested with NotI or SgrAI (Fig.…”
Section: Di¡erentiation Of the Strains At The Genomic Levelmentioning
confidence: 99%